Peningkatan Pemahaman Terkait Kedudukan Hukum Perjanjian Terapeutik Dalam Persetujuan Tindakan Medik Di Rumah Sakit Aulia Kota Pekanbaru: Increasing Understanding Regarding the Legal Position of Therapeutic Agreements in Approval of Medical Actions at Aulia Hospital Pekanbaru City - Indra Afrita Indra; Wilda Arifalina Wilda; Tri Anggara Putra Anggara (Institut Riset dan Publikasi Indonesia, 2021)
The problem found in community service activities is the lack of understanding of health workers in the Pekanbaru City Aulia Hospital regarding the Legal Position of Therapeutic Agreements in Approval of Medical Actions. They do not understand the Therapeutic agreement in detail and have a legal basis, especially the benefits and uses of the Therapeutic agreement for Health Workers.The solution offered in this service activity is to increase the understanding of Health Workers in the Pekanbaru City Aulia Hospital regarding the Legal Position of Therapeutic Agreements in Medical Action Agreements.The method of implementing this service activity is to use the lecture, dialogue, and discussion methods in the context of legal counseling about Increasing Understanding of the Legal Position of Therapeutic Agreements in Approval of Medical Actions at Aulia Hospital Pekanbaru City.The participation of partners in this community service activity is the management of the Aulia Hospital and also the health workers who play a role in carrying out this therapeutic agreement. Aulia Hospital contributes to providing a place and supporting facilities to carry out activities and bring health workers and management.The output targets of this community service activity are scientific articles which will later be published in national journals, as well as part of the implementation of the Tri Dharma of higher education.The conclusion is that this activity has been successfully implemented and the benefits can be felt for the participants. This can be seen from the participants' answers to the questionnaire given after the activity was carried out. After the activity was carried out, 98% of participants answered that they knew and understood the material presented.The suggestion is that activities with this theme should be carried out on an ongoing basis to health workers and management of the Pekanbaru City Aulia Hospital. Keywords: Agreement, Therapeutic Agreement.